Alteration of vasopressin-aquaporin system in hindlimb unloading mice - Ranieri, Marianna; Venneri, Maria; Storlino, Giuseppina; Ferrulli, Angela; D’Agostino, Mariagrazia; Centrone, Mariangela; Di Mise, Annarita; Zerlotin, Roberta; Tamma, Grazia; Grano, Maria; Valenti, Giovanna (Frontiers in Physiology, 2025)
Murine hindlimb unloading (HU) is considered a model of choice for simulating the physiological effects of microgravity on several functions, including fluid and electrolyte homeostasis. Microgravity causes changes in blood redistribution, modulating vasopressin secretion, a major hormone controlling water reabsorption through the vasopressin-sensitive water channel AQP2. In this study, mice were hindlimb suspended over 4 weeks or rested in the ground as controls, and vasopressin levels, along with renal aquaporins expression were investigated. Copeptin, a stable precursor of the hormone vasopressin, significantly increased as early as 1 week of unloading which correlated with a significant increase in AQP2 total protein expression and decrease in serum osmolality, suggesting early activation of the vasopressin/AQP2 axis in this model. Conversely, in 4 weeks HU suspended mice, copeptin decreased significantly and both AQP2 mRNA and AQP2 total protein expression were significantly reduced. Consistent with a downregulation of the vasopressin/AQP2 axis an increase in serum osmolality was observed at 4 weeks HU. The basolateral water channels AQP3 and AQP4 were, on the other hand, unaffected. Immunolocalization studies confirmed reduced expression of AQP2 in renal collecting ducts of HU mice at 4 weeks. A significantly increased amount of the expressed AQP2 was found phosphorylated at Ser261, a site regulating AQP2 protein stability and degradation. In line, p38-MAPK, committed to phosphorylate Ser261 and to increase miR137 expression, an AQP2 mRNA-targeted microRNA, was significantly increased in HU, suggesting that reduced AQP2 expression was mainly due to increased protein degradation and downregulation of AQP2-mRNA translation. Our results suggest that vasopressin/AQP2 axis is upregulated as early as 1 week and may be involved in the antidiuretic response also observed in early spaceflight period in astronauts. Contrariwise, the vasopressin-AQP2 system is downregulated after 4 weeks HU, likely to counteract the persistent central venous pressure due to cephalic shift of fluids.